Comfort in discomfort: The role of Somatic Practices in dance as a means to release trauma from the body - Sara Lind Guðnadóttir 2001- (2024)
In this essay, I will analyze the role of somatic practices in dance as a means of releasing trauma from the body. Drawing from my personal journey and exploration during the creation of my individual piece, titled "Comfort in discomfort," which was completed in the third and final year of my Bachelor of Arts in Contemporary Dance Practices at the Iceland University of the Arts. Incorporating principles from somatic practices, tension and trauma-releasing exercises (TRE), pleasure activism, and other somatic practices. The thesis explores how somatic techniques can be utilized to navigate and alleviate the effects of trauma. The culmination of this exploration led to a performance where the stage became a canvas for emotional expression, showcasing the raw authenticity of the performers' journeys translated into movement and interaction. This process has provided a powerful platform for healing for me and my performers, resulting in a profound shift in our understanding and connection with our bodies. We now possess a deeper awareness of how our trauma influences our physical being and have developed an effective approach to addressing it. Through this essay, I aim to guide readers through our journey and our exploration of integrating somatic practices into dance as a method of releasing trauma from our bodies, fostering understanding and engagement.